Strategi Pidato Pejabat dan Politisi Indonesia dalam Debat di Kanal YouTube Indonesia Lawyers Club - Fauzi Rahman; Zainal Rafli; Ifan Iskandar (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
In debating activities, especially political debates, a speaker does not always issue arguments in the same way. Sometimes the speaker conveys his ideas kindly and gently, sometimes with diction that seems to have negative connotations, sometimes even silent and says nothing. Therefore, this study will analyze in depth the speech strategies produced by Indonesian officials and politicians in a political debate on the YouTube channel. The method used is qualitative with a note-taking technique. The source of the research data used was speech from officials and politicians in a debate event on the Indonesia Lawyers Club (ILC) YouTube channel. Data analysis was carried out through transcription and interpretation of spoken strategies from Brown and Levinson. The results showed that an unceremonious strategy was used to chime in on insubstantial unceremoniously unceremonious speech opponents. Furthermore, positive civility strategies usually tend to be used in political policy debates by parties who support or represent political policyholders. The strategy of negative politeness in political debates is usually used by speakers from the opposition who provide criticism of political policies. Furthermore, vague strategies are used by speakers in political debates as a way to suppress and provide resistance to the ideas spoken, no matter whether the ideas of the speech partners are complete or not. Finally, there is no silent or silent strategy to speak silently.